Optimized Error Detection and Correction in ATM Networks Using the Enhanced Berlekamp Massey Algorithm With Hybrid Automatic Repeat Request - Aykac, Mahmut (IEEE access, 2025)
Asynchronous Transfer Mode (ATM) is a widely used communication method known for its high bandwidth features and low latency. It uses fixed size cells, namely 53 bytes, including 48 bytes for the real data and five bytes set for control purposes. To help in resolving any transmission issues, the control information contains components such as a Virtual Path Identifier (VPI), Virtual Channel Identifier (VCI), and Cyclic Redundancy Check (CRC). While Automatic Repeat Request (ARQ) can cause delays because of retransmissions, Forward Error Correction (FEC) improves efficiency by fixing errors without the need of data retransmissions. Reed-Solomon (RS) codes are widely used in ATM networks because of their ability in correcting burst errors. The proposed Enhanced Berlekamp Massey Algorithm (EBMA) improves RS error correction by updating only the essential polynomial coefficients. Not only the proposed algorithm cuts decoding complexity and processing time but also it makes it suitable for real time and modern communication networks like ATM. The simulation results confirm that the integration of EBMA and Hybrid Automatic Repeat Request (HARQ) succeeds remarkable gains in Bit Error Rate (BER) and power efficiency. Furthermore, a new adaptive algorithm has been developed that simplifies the process by dynamically modifying decoding parameters in real time according to channel conditions. This minimizes the need for unnecessary computations. The results show that EBMA can really improve the transmission reliability and data integrity in ATM networks.